PENGARUH GOOD CORPORATE GOVERNANCE DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN LINGKUNGAN (Studi Empiris pada Perusahaan Manufaktur dan Tambang yang Terdaftar pada Bursa Efek Indonesia (BEI) dan Termasuk dalam PROPER Tahun 2009-2011) - Agny Gallus Pratama; Rahardja Rahardja (Diponegoro Journal of Accounting, 2013)
The research was conducted on mining and manufacturing companies to determine the effect of GCG (Good Corporate Governance) that was proxied by (the proportion of independent board, board size, number of board meetings, and the size of the audit committee) and the environmental perfomance against corporate environmental disclosure. Issuance of PP No. 47 Tahun 2012 tentang